Acute kidney injury in Malaysian intensive care setting: incidences, risk factors and outcome - Md Ralib, Azrina; Nanyan, Suhaila; Ramly, Nur Fariza; Mat Nor, Mohd Basri (Wolters Kluwer Medknow Publications, 2018)
Introduction: Acute Kidney Injury (AKI) is common in the intensive care unit (ICU) with high risk of morbidity and mortality. The high incidence of AKI in our population may be attributed to sepsis. We investigated the incidence, risk factors and outcome of AKI in four tertiary Malaysian ICUs. We also evaluated its association with sepsis. Materials and Methods: This retrospective cohort study extracted de-identified data from the Malaysian Registry of Intensive Care in four Malaysian tertiary ICUs between January 2010 and December 2014. The study was registered under the NMRR and approved by the ethics committee. AKI was defined as twice the baseline creatinine or urine output < 0.5 ml/kg/h for 12 hours. Results: Of 26,663 patients, 24.2% had AKI within 24 hours of admission. Patients with AKI were older and had higher severity of illness compared to those without AKI. AKI patients had longer duration of mechanical ventilation, length of ICU and hospital stay. Age, SAPS II Score, and the presence of sepsis and preexisting hypertension, chronic cardiovascular disease independently associated with AKI. 32.3% had sepsis. Patients with both AKI and sepsis had highest risk of mortality (RR 3.43 (3.34 to 3.53)). Conclusions: AKI is common in our ICU, with higher morbidity and mortality. Independent risk factors of AKI include age, severity of illness, sepsis and preexisting hypertension, chronic cardiovascular disease. AKI independently contributes to mortality. The presence of AKI and sepsis increased the risk of mortality by three times.